Eating attitudes and behaviours in elite Canadian athletes with a spinal cord injury - Krempien, J. L.; Barr, S. I. (Eating Behaviors, 2012)
Athletes with a spinal cord injury (SCI) appear to have relatively modest energy requirements despite demanding training regimes. Virtually nothing is known about the factors which influence the energy intake of those with a SCI including food related attitudes and behaviours. Using a cross-sectional observational design, three aspects of eating attitudes were measured using the Three-Factor Eating Questionnaire (TFEQ) along with six days of self-reported dietary intake and anthropometrics. Between March 2007 and May 2009, a total of 32 Canadian athletes with a SCI (n = 24 men, n = 8 women) completed the study. The TFEQ scales showed a cognitive dietary restraint score of 10.8 ± 4.7, disinhibition score of 2.8 ± 1.8 and hunger score of 3.1 ± 2.2. When the group was split into high and low restraint groups using a median of 11.5, no differences were detected in any of the absolute parameters of reported dietary intake although the higher restraint group had protein intakes account for a greater proportion of total energy. Those with higher restraint scores also had a relatively higher disinhibition score. While the cognitive dietary restraint scores for the women were similar to other able-bodied populations, the scores for men were higher than population norms from other studies. The scores for disinhibition and hunger were lower than reported ranges from able-bodied subjects. These athletes may be actively monitoring or limiting dietary intake to avoid the high prevalence of obesity associated with a SCI or perhaps to maintain an ideal body composition for their sport performance.